Banting Memorial Lecture 2010^. Type 2 diabetes as an 'infectious' disease: is this the Black Death of the 21st century? - Matthews, DR; Matthews, P (2011)
We are currently facing a global pandemic of obesity and Type 2 diabetes. In some settings, the population prevalence of Type 2 diabetes is 50%, and half of those affected will die from diabetes-related complications. Eight centuries ago, an epidemic of bubonic plague swept across Europe, killing at least half of its victims. We here draw comparisons between these two pandemics, proposing close analogies between the 'Black Death' of the 14th century and the modern-day equivalent of Type 2 diabetes. Both diseases can be considered in terms of an aetiological agent, a reservoir, a vector and a predisposing toxic environment; populations can be considered as highly susceptible to the transmissable agents of Type 2 diabetes in the setting of calorie excess, inadequate food labelling, poorly regulated advertising and sedentary lifestyles. As for tackling a pandemic of a contagious microbial pathogen, we believe that breaking the cycle of transmission in the diabetes epidemic must be underpinned by political will and prompt, decisive legislation backed by the medical community. Far from fearing that such measures edge us towards a 'nanny state', we believe individuals should expect a responsible government to safeguard them from the toxic milieu that puts them at risk of obesity and its complications, and that communities and populations have the right to have their health protected.